2015
DOI: 10.3906/sag-1310-38
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of erdosteine, vitamin E, and vitamin C on renal injury induced by the ischemia-reperfusion of the hind limbs in rats

Abstract: Background/aim: To compare the protective efficacy of erdosteine and vitamins C and E against renal injury caused by hind limb ischemia-reperfusion (I/R).Materials and methods: Rats were split into 4 groups: group I as the control, group II as I/R, group III as I/R + erdosteine, and group IV as I/R + vitamins C and E. Superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) activities and malondialdehyde (MDA) tissue levels were determined.Results: MDA levels were found comparable with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…24 This cellular dysfunction and disintegrity might play a role in the etiopathology of remote organ damage including liver, kidney and lung in lower limb ischemia-reperfusion injury. [3][4][5]16 The kidneys are particularly involved in the remote alteration phenomenon following skeletal muscle ischemia-reperfusion injuries. 23 Although a diversity of mechanisms exist, oxidative stress, inflammatory response, and the apoptosis are believed to be the primary causes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 This cellular dysfunction and disintegrity might play a role in the etiopathology of remote organ damage including liver, kidney and lung in lower limb ischemia-reperfusion injury. [3][4][5]16 The kidneys are particularly involved in the remote alteration phenomenon following skeletal muscle ischemia-reperfusion injuries. 23 Although a diversity of mechanisms exist, oxidative stress, inflammatory response, and the apoptosis are believed to be the primary causes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several animal studies showed that hind limb I/R injury affected several organs, including the kidneys, liver and lungs. [3][4][5] The highly selective and potent a2-adrenergic agonist dexmedetomidine (DXM) is an effective sedative, anxiolytic, and analgesic agent 6 with protective effects against I/R injury in several organs, including the heart, 7 brain, 8 and kidneys, 9 probably due to the antioxidant and anti-inflammatory properties of the compound. [10][11][12] Curcumin (CUR) has a long history of therapeutic use in Indian and Chinese medicine and has several pharmacological properties, including antioxidant, anti-inflammatory, antiviral, antimicrobial, antifungal, as well as anticancer activities.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolites of erdosteine have two sulfhydryl groups and they take part in free radical scavenging and antioxidant activity (13). Free radical scavenging properties of erdosteine have been shown in experimental and clinical studies (1,6,7,11).…”
Section: Discussionmentioning
confidence: 99%
“…If blood flow is reestablished after reperfusion, substances produced as a result of oxidation may unexpectedly induce increased rates of mortality and morbidity because of systemic complications. Following local edema and muscle tissue necrosis, systemic inflammatory response syndrome and multiple organ failure (e.g., kidney, respiratory, and circulatory systems) generally occur as reperfusion accelerates (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation